Perkembangan Kekuasaan Bani Abbas - Aziizah, Puan (Maliki Interdisciplinary Journal, 2025)
The Abbasid Dynasty, established in 750 CE and ruling until 1258 CE, replaced the Umayyad Dynasty as the Islamic Caliphate and moved the capital from Kufa to Baghdad, which became the center of governance and civilization. This dynasty was named after Al-Abbas, the uncle of Prophet Muhammad, giving them a strong claim as the legitimate successors to the caliphate. During the Abbasid period, the pinnacle of Islamic teachings was achieved through advancements in various fields, though not without conflicts. The Abbasids, claiming the right to the caliphate due to their closer lineage to the Prophet, believed that the Umayyads were illegitimate and lacked adherence to Islamic principles. This dissatisfaction was fueled by the Umayyads’ governance methods, which were perceived as coercive and inconsistent with Islamic teachings. The Abbasids’ efforts to seize the caliphate through underground movements and garnering support eventually established the Abbasid Dynasty as the second caliphate in Islamic history, succeeding the Rashidun Caliphate, which had similarly experienced cycles of growth and decline.